Meat Species Identification in Chicken Blood Meal using Polymerase Chain Reaction Technique (Indian Journal of Animal Production and Management, 2024)
A study was conducted to identify the species of chicken in high heat processed chicken  secondary by-product comprising of poultry blood meal. A total of 30 samples of poultry  blood meal were collected from different poultry processing plants in Tamil Nadu. Species  specific polymerase chain reaction was employed to validate the meat species  identification in heat processed secondary poultry by-products. Custom designed primer  sequences of mitochondrial cyt b gene were utilised for the present study. The results  revealed successful amplification of chicken species at 227 base pairs in samples of all the  blood meal samples. Thus, it was concluded that species specific polymerase chain  reaction technique can be effectively used in the screening of chicken meat species in  different heat processed secondary by-products for quick and reliable results.
Keywords: cyt b gene; chicken; blood meal; polymerase chain reaction